Suppression of biofilm formation on selected plant pathogenic fungi using commercial fungicide - Soh, Sudamma Chien Hsien (2017)
Plant pathogenic fungi are the fungus that brings harm to many plant species by reducing quality and yield of plant produces. Fusarium spp. are toxin producers, endophytes and saprotrophs as well as biofilm producers. Biofilm formation is the coordination action of multiple strains that helps and protects each other. Thus, the objective of this study is to assess efficacy of commercial fungicide to suppress formation of biofilm on selected plant pathogenic fungi. In this study, Carbendazim was used to suppress biofilm formation and mycelial growth of Fusarium oxysporum, F. solani, Pyricularia oryzae and Phytophthora palmivora. Microtiter plate and poison media methods were used to evaluate the efficacy of the tested fungicide on the fungi in vitro. Five concentrations i.e. 0 ppm (control), 10 ppm, 50 ppm, 100 ppm and 200 ppm were assigned for the poison media method. Results from poison media method showed that Carbendazim promoted significant (P ≤ 0.05) inhibition on mycelial growth of the fungi. Carbendazim displayed 100% mycelial inhibition on F. oxysporum and P. oryzae at concentration of 200 ppm. However, for microtiter plate method, Carbendazim was found to be not effective in suppressing the growth of biofilm in fungi F. oxysporum and F. solani due to the strong natural resistance formed by fungal biofilm when there was presence of fungicide. Therefore, in this study, Carbendazim was only effective in disrupting the mycelial growth of fungi and not the fungal biofilm.